Emulsifiers: Effects on Quality of Fibre-Enriched Wheat Bread - Gómez, Analía Verónica (2012)
Resistant starch (RS) is a nutritional ingredient commonly used in bread products as dietary fibre (DF). This ingredient presents similar physiological functions than those imparted by DF, promoting beneficial effects such as the reduction of cholesterol and/or glucose levels on blood. Quality improvement of bread containing RS, with an optimized combination of emulsifiers, will be useful in the development of new and healthy bakery products. The objective of this research was to analyse the effects of different emulsifiers on several quality parameters of dough and bread prepared with wheat flour partially substituted with resistant starch as a dietary fibre. A blend of wheat flour/maize-resistant starch (MRS; 87.5:12.5) with sodium chloride, ascorbic acid, α-amylase, compressed yeast and water was utilized. Emulsifiers were incorporated to formulations in different levels according to a simplex centroid design. The viscoelastic, textural and extensional properties of dough were analysed. Bread quality was evaluated throughout the gelatinization and retrogradation of starch, specific volume of loaves, and texture and firmness of bread crumb. The incorporation of 12.5% (w/w) of MRS to wheat flour caused an increase of 5% in water absorption. Stability decreases markedly (from 9.9 to 2.2 min) and the mixing tolerance index increased (from 79 to 35 UF). The sodium stearoyl lactylate (SSL)–diacetyl tartaric acid esters of monoglycerides (DATEM) mixture increased hardness and resistance to extension on dough, whilst dough containing Polysorbate 80 (PS80) was softer; nevertheless, both types of dough retained less CO2. An optimized concentration of the three emulsifiers (0.24% SSL, 0.18% PS80, 0.08% DATEM, w/w) was obtained by surface response methodology. The bread prepared with this combination of emulsifiers presented a considerable specific volume with a very soft crumb.